A novel mutation in L1CAM causes a mild form of L1 syndrome: a case report. Issue 8 (15th June 2017) - Otter, Maarten; Wevers, Marijke; Pisters, Marline; Pfundt, Rolph; Vos, Yvonne; Nievelstein, Rutger Jan; Stumpel, Constance
Key Clinical Message: Clinical geneticists, neurologists, psychiatrists, and other healthcare providers can learn from this case report that patients with a behavioral phenotype that includes a mild learning disability may also require a thorough examination, including brain MRI and whole‐exome sequencing. Abstract : Clinical geneticists, neurologists, psychiatrists, and other healthcare providers can learn from this case report that patients with a behavioral phenotype that includes a mild learning disability may also require a thorough examination, including brain MRI and whole‐exome sequencing.